2015
DOI: 10.1186/s12959-015-0035-3
|View full text |Cite|
|
Sign up to set email alerts
|

Oral rivaroxaban for Japanese patients with symptomatic venous thromboembolism – the J-EINSTEIN DVT and PE program

Abstract: BackgroundThe global EINSTEIN DVT and PE studies compared rivaroxaban (15 mg twice daily for 3 weeks followed by 20 mg once daily) with enoxaparin/vitamin K antagonist therapy and demonstrated non-inferiority for efficacy and superiority for major bleeding. Owing to differences in targeted anticoagulant intensities in Japan, Japanese patients were not enrolled into the global studies. Instead, a separate study of deep vein thrombosis (DVT) and/or pulmonary embolism (PE) in Japanese patients was conducted, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 25 publications
10
86
1
1
Order By: Relevance
“…At the end of the treatment, 62% of the patients in the rivaroxaban group and 31.6% in the UFH+VKA group exhibited normalization on examinations. 22 In our study, examinations of patients after 30 days of treatment revealed partial or total recanalization rates of 10% and 55.3% in Groups I (heparin + warfarin) and II (rivaroxaban), respectively. At the end of the J-EINSTEIN-DVT/PE study, 95.8% of the patients in the rivaroxaban group exhibited improvement or normalization on examinations, compared to 89.5% of patients treated with UFH+VKA.…”
Section: Discussionsupporting
confidence: 49%
“…At the end of the treatment, 62% of the patients in the rivaroxaban group and 31.6% in the UFH+VKA group exhibited normalization on examinations. 22 In our study, examinations of patients after 30 days of treatment revealed partial or total recanalization rates of 10% and 55.3% in Groups I (heparin + warfarin) and II (rivaroxaban), respectively. At the end of the J-EINSTEIN-DVT/PE study, 95.8% of the patients in the rivaroxaban group exhibited improvement or normalization on examinations, compared to 89.5% of patients treated with UFH+VKA.…”
Section: Discussionsupporting
confidence: 49%
“…Of these 13 trials, eight were classified as high quality based on rigorous randomization, allocation concealment, blinding and outcome reporting without potential bias. There were four studies at high risk of bias due to their open‐label design (EINSTEIN‐DVT , EINSTEIN‐PE , J‐EINSTEIN‐DVT/PE and RE‐LY ). One study did not report the method used to generate the randomization sequence and allocation concealment, and the risk of bias was judged as unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen phase III RCTs were included in qualitative and quantitative synthesis. The trials investigated dabigatran (n = 4 [15][16][17][18]), rivaroxaban (n = 5 [19][20][21][22][23]), apixaban (n = 2 [24,25]) and edoxaban (n = 2 [26,27]). Across the 13 trials, 58 021 patients were randomly assigned to receive DOAC and 44 822 to receive warfarin (or heparin/low-molecular-weight heparin, followed by warfarin).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The J-EINSTEIN DVT and PE program assessed the effectiveness of rivaroxaban compared with standard therapy in 100 consecutive Japanese patients with objectively confirmed proximal DVT and/or PE. 40) This open-label, randomized, multicenter trial showed that neither rivaroxaban (15 or 10 mg bid for 21 days followed by 15 mg once-daily) nor standard therapy (UFH/warfarin) caused any major bleeding events. On day 22 of treatment, repeat imaging showed the complete absence of thrombi in 26.7% of rivaroxaban patients compared with 15.8% of those treated with standard therapy, but the results were not statistically significant owing to patient numbers.…”
Section: )mentioning
confidence: 94%
“…On day 22 of treatment, repeat imaging showed the complete absence of thrombi in 26.7% of rivaroxaban patients compared with 15.8% of those treated with standard therapy, but the results were not statistically significant owing to patient numbers. 40) Additional subanalyses of the phase III EINSTEIN datasets have enhanced our understanding of the early effects of high-dose NOAC treatment on thrombus resolution in patients with PE. A predefined safety analysis of PE thrombus resolution in an initial cohort of patients in the EINSTEIN PE study showed a reduction in vascular obstruction.…”
Section: )mentioning
confidence: 99%